2018
DOI: 10.48550/arxiv.1802.09464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-Goal Reinforcement Learning: Challenging Robotics Environments and Request for Research

Abstract: The purpose of this technical report is two-fold. First of all, it introduces a suite of challenging continuous control tasks (integrated with OpenAI Gym) based on currently existing robotics hardware. The tasks include pushing, sliding and pick & place with a Fetch robotic arm as well as in-hand object manipulation with a Shadow Dexterous Hand. All tasks have sparse binary rewards and follow a Multi-Goal Reinforcement Learning (RL) framework in which an agent is told what to do using an additional input. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
211
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(213 citation statements)
references
References 14 publications
2
211
0
Order By: Relevance
“…We represent the same problem setup, that of multiple tasks with multiple goals per task, in a robotic continuous space environment. We choose to adapt the FetchReach-v0 environment from Plappert et al (2018) in order to train an agent to move a robotic gripper close to a set of target positions in the correct order. We represent all the multiple goal positions in the input space by 3D coordinates, sampled around the gripper starting position.…”
Section: A25 Fetchreach Experiments: Implementation Detailsmentioning
confidence: 99%
“…We represent the same problem setup, that of multiple tasks with multiple goals per task, in a robotic continuous space environment. We choose to adapt the FetchReach-v0 environment from Plappert et al (2018) in order to train an agent to move a robotic gripper close to a set of target positions in the correct order. We represent all the multiple goal positions in the input space by 3D coordinates, sampled around the gripper starting position.…”
Section: A25 Fetchreach Experiments: Implementation Detailsmentioning
confidence: 99%
“…This domain is adapted from the well known gym robotics FetchPickAndPlace-v0 environment [38]. The following modifications were made: 1) 3 additional blocks were introduced, with different colours, and a goal pad, 2) object spawn locations were not randomized and were instantiated equidistantly around the goal pad, see Fig.…”
Section: Environmentsmentioning
confidence: 99%
“…Prior works have shown that a standard off-policy algorithm DDPG [6] combined with an implicit curriculum method HER [7] can learn dexterous manipulation policies to control an object with simple geometries, such as a cube or an egg [8]. However, whether a single policy can work well on a large number of geometrically-diverse objects has been under-explored.…”
Section: Geometry-aware Multi-task Learningmentioning
confidence: 99%
“…Because the object geometries are vastly different from each other, leading to different levels of difficulties for the manipulation policies, a random split may not ensure fair evaluations. Therefore, we use the same DDPG + HER algorithm to train an oracle single-task RL policy for each object, following the setup from [8]. Then we split the objects according to the success rate of its oracle, ensuring that the training and held-out objects have similar difficulties on average.…”
Section: B Train/test Splitmentioning
confidence: 99%
See 1 more Smart Citation